Moral Distress in the Neonatal Intensive Care Unit: What Is It, Why It Happens, and How We Can Address It - Mills, Manisha; Cortezzo, DonnaMaria E. (Frontiers in Pediatrics, 2020)
Moral distress is prevalent in the neonatal intensive care unit, where decisions regarding end-of-life care, periviable resuscitation, and medical futility are common. Due to its origins in the nursing literature, moral distress has primarily been reported among bedside nurses in relation to the hierarchy of the medical team. However, it is increasingly recognized that moral distress may exist in different forms than initially described and that healthcare professions outside of nursing experience it. Advances in medical technology have allowed the smallest, sickest neonates to survive. The treatment for critically ill infants is no longer simply limited by the capability of medical technology but also by moral and ethical boundaries of what is right for a given child and family. Shared decision-making and the zone of parental discretion can inform and challenge the medical team to balance the complexities of patient autonomy against harm and suffering. Limited ability to prognosticate and uncertainty in outcomes add to the challenges faced with ethical dilemmas. While this does not necessarily equate to moral distress, subjective views of quality of life and personal values in these situations can lead to moral distress if the plans of care and the validity of each path are not fully explored. Differences in opinions and approaches between members of the medical team can strain relationships and affect each individual differently. It is unclear how the various types of moral distress uniquely impact each profession and their role in the distinctively challenging decisions made in the NICU environment. The purpose of this review is to describe moral distress and the situations that give rise to it in the NICU, ways in which various members of the medical team experience it, how it impacts care delivery, and approaches to address it.